Can AI Predict COPD Exacerbations? A Deep Dive into Digital Health - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Chronic Obstructive Pulmonary Disease COPD is a major global health challenge, characterized by persistent respiratory symptoms and airflow limitation. A cri...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Precision Medicine; Machine Learning